기계번역에 관한 대학생의 인식과 사용 양상 - 강지혜; 이영희 (번역학연구, 2024)
As machine translation (MT) becomes increasingly integrated into various aspects of everyday life, understanding how university students perceive and utilize these tools is essential for fostering their effective, critical, and reflective engagement with MT. This study investigates university students’ perceptions and usage patterns of MT, aiming to inform guidelines for MT use in higher education and establish training programs to enhance students’ MT literacy, covering its fundamentals, benefits, and potential risks. A comprehensive survey of 464 students from various academic fields at a major South Korean university revealed that MT is used frequently and extensively across all disciplines. The main factors contributing to its widespread use are efficiency and accessibility, with academic support being its most wide application. However, significant differences were observed in the preferred MT tools and post-editing methods, depending on their affiliated fields. Despite these variations, the overall usage patterns and motivations for employing MT were remarkably similar across academic divisions. These findings highlight the critical role of MT in academic settings and underscore the need for MT literacy to be included as a key component of university education. Targeted educational initiatives should be developed to maximize the benefits of MT tools while enhancing students’ understanding of their limitations and ethical issues.
Keywords: Machine translation (MT); perceptions of MT; MT use; usage survey; higher education; MT literacy; 기계번역; 기계번역에 관한 인식; 기계번역 사용; 사용자 인식조사; 대학 교육; 기계번역 문해력